Line of duty. Series 5 [videorecording (DVD)] - Graham, Stephen, 1973-; Compston, Martin; McClure, Vicky, 1983-; Dunbar, Adrian, 1958- (Acorn Media, 2019)
Series follows anti-corruption unit 12 (AC-12) as they investigate fellow police officers accused of corruption. In series five, Stephen Graham stars as John Corbett, the ruthless leader of an organized crime group who hijacks a seized drugs transport. AC-12 investigators suspect corrupt police officers of leaking information. As the body count rises, AC-12 realize they₂re facing their most vicious adversary yet.